Spatially Selective Electrochemical Cleavage of a Polymerase-Nucleotide Conjugate - Smith, Jake; Nguyen, Bichlien; Carlson, Rob; Bertram, Jeffrey G.; Palluk, Sebastian; Arlow, Daniel H.; Strauss, Karin (ACS Synthetic Biology, 2023)
Novel enzymatic methods are poised to become the dominant processes for de novo synthesis of DNA, promising functional, economic, and environmental advantages over the longstanding approach of phosphoramidite synthesis. Before this can occur, however, enzymatic synthesis methods must be parallelized to enable production of multiple DNA sequences simultaneously. As a means to this parallelization, we report a polymerase-nucleotide conjugate that is cleaved using electrochemical oxidation on a microelectrode array. The developed conjugate maintains polymerase activity toward surface-bound substrates with single-base control and detaches from the surface at mild oxidative voltages, leaving an extendable oligonucleotide behind. Our approach readies the way for enzymatic DNA synthesis on the scale necessary for DNA-intensive applications such as DNA data storage or gene synthesis.